Market profile and performance analysis of cultured fish actors - Ololade Rachel A; Olagunju Funke I; Adeojo John R; Adejumo Taiwo J (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2023)
Cultured fish marketing is highly entrepreneurial. It is a highly perishable commodity that deteriorates very rapidly, rendering it unfit for human consumption if kept for a long time without processing. This study aims to examine the performance of cultured fish actors (producers, processors, wholesalers, and retailers involved in the selling of fish), identify the factors influencing their performance, and identify constraints of the cultured fish market in the study area. Primary data on socioeconomic and resource characteristics were collected with the use of a structured questionnaire administered to 300 respondents using a multistage random sampling technique among cultured fish actors in South-Western Nigeria. The data were analyzed using descriptive statistics for the market profile of the actors, Market Margin (MM) estimations for the performance of actors, and multiple regression for factors affecting the performance of actors. The analyses showed that 81.70%, 37.93%, 51.47%, and 27.03% of the producers, processors, wholesalers, and retailers respectively were males. The analysis of the performance of actors showed that the Gross Profit Margin (GPM) for the producers, processors, wholesalers, and retailers are 75.26%, 16.21%, 7.63%, and 0.9%, respectively. The multiple regression results showed that the significant factors affecting the performance of actors were transport cost (p = 0.000), labour cost (p = 0.001), cost of fish purchased (p = 0.073), cost of fish sold (p = 0.000), the quantity of fish sold (p = 0.000) and access to credit (p = 0.085). Inadequate funds/capital, poor electricity, lack of good roads, and a market for the produce are the major constraints of cultured fish marketing in the study area. Conclusively, the GPM showed that the actors were all making a profit but at different rates because the cost incurred by each actor differs.